The effect of professional commitment and ethical consideration on the desire to do whistleblowing with locus of control as a moderating variable (study on the banking sector in Palembang) - Inten Meutia; Mohamad Adam; Tiara Nurpratiwi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study aims to obtain empirical evidence regarding the effect of professional commitment and ethical considerations on the desire to conduct whistleblowing. This study also adds locus of control as a moderating variable that influences the relationship between professional commitment and ethical considerations. Respondents in this study were 53 internal auditors placed in the banking operational unit in Palembang and sampling by saturated sample method. The results of this study indicate: (1) The professional commitment of internal auditors has a positive effect on the desire to conduct whistleblowing, (2) Ethical considerations of internal auditors have a positive effect on the desire to conduct whistleblowing, 3) professional commitment of internal auditors moderated Locus of control does not affect desire do whistleblowing, and 4) ethical considerations of internal auditors moderated locus of control does not affect the desire to do whistleblowing.